SLC26A4 targeted to the endolymphatic sac rescues hearing and balance in Slc26a4 mutant mice. - Xiangming Li; Joel D Sanneman; Donald G Harbidge; Fei Zhou; Fei Zhou; Taku Ito; Raoul Nelson; Nicolas Picard; Régine Chambrey; Dominique Eladari; Tracy Miesner; Andrew J Griffith; et al. (PLoS Genetics)
Mutations of SLC26A4 are a common cause of human hearing loss associated with enlargement of the vestibular aqueduct. SLC26A4 encodes pendrin, an anion exchanger expressed in a variety of epithelial cells in the cochlea, the vestibular labyrinth and the endolymphatic sac. Slc26a4 (Δ/Δ) mice are devoid of pendrin and develop a severe enlargement of the membranous labyrinth, fail to acquire hearing and balance, and thereby provide a model for the human phenotype. Here, we generated a transgenic mouse line that expresses human SLC26A4 controlled by the promoter of ATP6V1B1. Crossing this transgene into the Slc26a4 (Δ/Δ) line restored protein expression of pendrin in the endolymphatic sac without inducing detectable expression in the cochlea or the vestibular sensory organs. The transgene prevented abnormal enlargement of the membranous labyrinth, restored a normal endocochlear potential, normal pH gradients between endolymph and perilymph in the cochlea, normal otoconia formation in the vestibular labyrinth and normal sensory functions of hearing and balance. Our study demonstrates that restoration of pendrin to the endolymphatic sac is sufficient to restore normal inner ear function. This finding in conjunction with our previous report that pendrin expression is required for embryonic development but not for the maintenance of hearing opens the prospect that a spatially and temporally limited therapy will restore normal hearing in human patients carrying a variety of mutations of SLC26A4.